Gamification Project-Based E-learning in Character Education: A Study in Senior High School - Merliana, Ni Putu Eka; Widyantara, I Made Oka; Wirastuti, Ni Made Ary Esta Dewi; Saputra, Komang Oka; Setyohadi, Djoko Budiyanto (JOIV : International Journal on Informatics Visualization, 2025)
E-learning in education faces challenges in improving students' engagement, specifically regarding character education effectiveness. Gamification is among the strategies that can be applied to increase student engagement in the project-based learning process. Therefore, this study aimed to develop a Gamification Framework for Project-Based E-learning in Character Education (GaPolCE) as an innovative solution to improve engagement and character education at the senior high school level. A quantitative study was carried out using a quasi-experimental method, where data collection was carried out through a pre-post test and log data analysis to measure the effectiveness of gamification in achieving character education and student engagement. The results showed that the implementation of GaPolCE improved aspects of character education measured using the N-Gain score, where moral knowledge was in the high category (0.70) while moral feeling (0.49) and moral action (0.51) were in the moderate category. Student engagement increased significantly by 67%, 8%, and 25% for behavioral, emotional, and cognitive engagement. However, the effectiveness of in-depth character formation requires long-term evaluation. In addition, the assessment of the application of gamification in project learning for character education is still done manually, thus increasing teachers' workload. In this regard, further research is needed with a longitudinal approach to ensure the sustainability of its influence. In addition, it is necessary to develop an automatic assessment system based on artificial intelligence to increase the efficiency of character education evaluation.